Magnetic stimulation of gold fiducial markers used in Image-Guided Radiation Therapy: Evidences of hyperthermia effects. (February 2020) - Arosio, Paolo; Avolio, Matteo; Gargano, Marco; Orsini, Francesco; Gallo, Salvatore; Melada, Jacopo; Bonizzoni, Letizia; Ludwig, Nicola; Veronese, Ivan
Highlights: IGRT Gold fiducial markers release heat if stimulated with magnetic field of MFH. Temperature distribution mapping of fiducial markers in tissue-mimicking phantoms. The temperature near the gold fiducial markers may induce thermal ablation. Checking position of gold marker prevents health tissue damage in combined MFH/IGRT. Abstract: A promising approach in oncology consists in combining Radiation Therapy (RT) with Magnetic Fluid Hyperthermia (MFH). Modern day RT takes advantage by imaging techniques able to provide information about the correct patient set-up, target position and movement during the treatments. For these purposes, gold fiducial markers, implanted into the tumors, or in their proximity, are used in the so-called Image-Guided Radiation Therapy (IGRT). In this study, hyperthermia produced by different gold fiducial markers under the application of an alternating magnetic field in the typical conditions used in Magnetic Fluid Hyperthermia (MFH) clinical trials was investigated. The temperature increase of different types of gold fiducial markers and of tissue mimicking hydrogel phantoms containing the fiducials were measured during the magnetic stimulation by means of a high-resolution thermal camera and a fiber optic temperature sensor. The results demonstrated that, within few tens of seconds after the start of the magnetic stimulation, the gold fiducial markers might reach temperatures higher than 70 °C. Local increases of the hydrogel temperature to values higher than 45 °C were also measured. These evidences highlight the need to evaluate carefully the presence and location of gold fiducial markers in patients undergoing combined IGRT and MFH treatments in order to prevent any thermal ablation of health tissues surrounding the markers.